The Effect of Job Satisfaction and Motivation on the Organizational Commitment - Nurlina, Nurlina; Widayatsih, Tri; Lestari, Neta Dian (Graduate Program Magister Manajemen Pendidikan, 2023)
This study determined the effect of job satisfaction and motivation on the organizational commitment of school principals in Palembang City. The research sample is 90 respondents. The technique of data collection in this research is to use a questionnaire and documentation technique. The results showed that the organizational commitment of the director is an important factor because; 1) the principal is the spearhead for the success of basic education management, without a strong organizational commitment, the principal will not properly perform his duties according to his responsibilities so the primary school goals will be difficult to achieve; 2) the organizational commitment of the director is a high level of trust in the organization, individuals who trust the organization will certainly be loyal and actively participate in their organization; 3) the organizational commitment of the current director is one last thing that cannot be improved because as an individual human being, the director will always grow and change according to the demands of the stakeholders. Therefore, primary school principals can improve themselves by increasing their organizational commitment to achieve organizational expectations and goals. In addition to this, this commitment affects job satisfaction and motivation for both yourself and the environment around you, of course, with greater satisfaction, job motivation can be seen from the organizational commitment of the director, which will have a good or positive impact on the world, of education. Therefore, based on the results of the study, there was a significant influence between job satisfaction and motivation in the organizational commitment of the principal of public primary schools in the city of Palembang.